Formulation, in-vitro & in-vivo evaluation of Ethyl cellulose microspheres of Glipizide - Sharma, Maya; Choudhury, P K (Journal of Drug Delivery and Therapeutics, 2019)
Objective: The objective of the present study was to formulate sustained release glipizide loaded microspheres and evaluate the effect of various variables on their properties.Materials and Methods: The microspheres were prepared by non solvent addition coacervation method. Ethyl cellulose used as a polymer, petroleum ether (60-40º) for induced coacervation and n-hexane as non solvent for microspheres preperation.Results: Microspheres were characterized in term of percent yield, percent entrapment and release pattern of drug. The shape, color and particle size of microspheres were also evaluated. According the result of formulation, n-hexane used as non solvent resulted in enhances rigidization of coating and petroleum ether (60-40º) for induced coacervation. The maximum percent yield of GEN6 formulation was 75.7; particle size in the range of 50-450 µ, maximum entrapment was 89.8 ± 0.11% for GEN3 formulation. GEN1 formulation with low polymer ratio showed better in-vitro release between 95-100%.  Formulation GEN4 showed 40-50% reduction in plasma glucose level than conventional dosage forms when tested in-vivo.Conclussion: Result of the present study supported that the formulation showed sustenance release with the potential application of n-hexane for improving the physical properties as well as the release profile of this water insoluble drug.